PENERAPAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN HASIL BELAJAR GULING DEPAN TUNGKAI BENGKOK - Gilang Abdi Wisnu Pradana; Agus Margono (PJKR FKOR UNS, 2018)
The purpose of this study is to improve the student’s achievement in gymnastic floor of crooked legs forward rolling in X-4 Senior High School Kebakkramat in academic year 2016/2017.This research is classroom action research that was done in two cycles, each cycles consist of two meetings. Subject of this research is the students of X-4 grade that consisted of 36 students. The data’s source collecting from the students, teachers, and the researcher. Techniques of data’s collection used test and observation. Data validity using data triangulation technique. Data analysis using qualitative descriptive analysis technique with percentage technique. The result of data analysis showed there is improvement of student’s learning outcomes in gymnastic floor of crooked legs forward rolling. In pracycles the precentage of the completness is 41,67% or 15 students, not completed yet 58,33% or 21 students. In first cycles the precentage of the completness is 63,88% or 23 students, not completed yet 36,11% or 13 students. In second cycles the percentage of the completness is 83,33% or 30 students, not completed yet 16,66% or 6 students. The learning result of gymnastic floor crooked legs of forward rolling has been reached according the expectation in second cycles with minimum criteria 75 Based on result analysis above we get the conclusion that the implementation of example non example improved the result learning of forward rolling of crooked legs in students of Senior High School Kebakkramat academic year 2016/2017.